Prospective Study of Cancer Genetic Variants: Variation in Rate of Reclassification by Ancestry. (1st April 2018) - Slavin, Thomas P; Van Tongeren, Lily R; Behrendt, Carolyn E; Solomon, Ilana; Rybak, Christina; Nehoray, Bita; Kuzmich, Lili; Niell-Swiller, Mariana; Blazer, Kathleen R; Tao, Shu; Yang, Kai; Culver, Julie O; et al.
Abstract: Background: In germline genetic testing, variants from understudied ancestries have been disproportionately classified as being of uncertain significance. We hypothesized that the rate of variant reclassification likewise differs by ancestry. Methods: Nonbenign variants in actionable genes were collected from consenting subjects undergoing genetic testing at two Southern California sites from September 1996 through December 2016. Variant reclassifications were recorded as they were received, until February 2017 or reclassification to benign. Excluding duplicate variants (same ancestry, laboratory, classification), generalized linear models for the hereditary breast cancer genes ( BRCA1/2 ) and other variants investigated whether rate of reclassification differed for seven categories of ancestry compared with non-Hispanic European. Models took into account laboratory, year, gene, sex, and current classification (handled as a time-dependent covariate) and were adjusted for multiple hypothesis testing. Results: Among 1483 nonbenign variants, 693 (46.7%) involved BRCA1/2 . Overall, 268 (18.1%) variants were reclassified at least once. Few (9.7%) reclassified variants underwent a net upgrade in pathogenicity. For BRCA1/2 variants, reclassification rates varied by ancestry and increased over time, more steeply for ancestries with lower initial rates (African, Ashkenazi, Chinese) than for ancestries whose initial rates were high (Middle Eastern) or similar to non-Hispanic European (non-Chinese Asian, Native American, Hispanic). In contrast, reclassification rates of non- BRCA1/2 variants did not vary over time but were elevated for most minority ancestries except non-Chinese Asian and Native American. Conclusions: For nonbenign variants in cancer-related genes, the rates at which reclassifications are issued vary by ancestry in ways that differ between BRCA1/2 and other genes.